SPAG17 mediates nuclear translocation of protamines during spermiogenesis - Agudo-Rios, Clara; Rogers, Amber; King, Isaiah; Bhagat, Virali; Nguyen, Le My Tu; Córdova-Fletes, Carlos; Krapf, Diego; Strauss, Jerome F.; Arévalo, Lena; Merges, Gina Esther; Schorle, Hubert; Roldan, Eduardo R. S.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Protamines (PRM1 and PRM2) are small, arginine-rich, nuclear proteins that replace histones in the final stages of spermiogenesis, ensuring chromatin compaction and nuclear remodeling. Defects in protamination lead to increased DNA fragmentation and reduced male fertility. Since efficient sperm production requires the translocation of protamines from the cytoplasm to the nucleus, we investigated whether SPAG17, a protein crucial for intracellular protein trafficking during spermiogenesis, participates in protamine transport. Initially, we assessed the protein-protein interaction between SPAG17 and protamines using proximity ligation assays, revealing a significant interaction originating in the cytoplasm and persisting within the nucleus. Subsequently, immunoprecipitation and mass spectrometry (IP/MS) assays validated this initial observation. Sperm and spermatids from Spag17 knockout mice exhibited abnormal protamination, as revealed by chromomycin A3 staining, suggesting defects in protamine content. However, no differences were observed in the expression of Prm1 and Prm2 mRNA or in protein levels between testes of wild-type and Spag17 knockout mice. Conversely, immunofluorescence studies conducted on isolated mouse Nuclear translocation of protamines 2 spermatids unveiled reduced nuclear/cytoplasm ratios of protamines in Spag17 knockout spermatids compared to wild-type controls, implying transport defects of protamines into the spermatid nucleus. In alignment with these findings, in vitro experiments involving somatic cells, including mouse embryonic fibroblasts, exhibited compromised nuclear translocation of PRM1 and PRM2 in the absence of SPAG17. Collectively, our results present compelling evidence that SPAG17 facilitates the transport of protamines from the cytoplasm to the nucleus.